ORGANIZATION OF MATHEMATICS LESSONS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article discusses the theoretical and practical aspects of organizing mathematics lessons effectively. It analyzes the structure and main stages of the lesson, as well as the use of modern pedagogical technologies and interactive methods. The importance of the competency-based approach and STEAM education in teaching mathematics is also highlighted.